The Role of Financial Access, Entrepreneurial Education, and Social Capital on SME Growth - Lestari Wuryanti; Mohamad Yusuf Golam; Diana Wangania; Christian Tarandung (Journal Management & Economics Review (JUMPER), 2026)
This study examines the role of financial access, entrepreneurial education, and social capital in influencing SME growth. Small and Medium Enterprises (SMEs) play a critical role in economic development, yet many face significant barriers to sustainable expansion, particularly in terms of capital constraints, limited managerial capability, and weak business networks. Using a quantitative research design with a cross-sectional survey of 210 SME owners and managers, this study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The results indicate that financial access, entrepreneurial education, and social capital all have positive and significant effects on SME growth. Among these variables, entrepreneurial education emerges as the strongest predictor, highlighting the central role of human capital in enhancing business performance. Furthermore, the findings reveal that entrepreneurial education partially mediates the relationship between financial access and SME growth, suggesting that financial resources generate greater impact when accompanied by managerial knowledge and skills. The structural model explains 67% of the variance in SME growth, demonstrating substantial explanatory power. These findings imply that SME development policies should adopt an integrated approach that combines improved financial inclusion, entrepreneurship education programs, and strengthened networking opportunities to foster sustainable business expansion. This study contributes to the literature by providing a comprehensive framework that integrates financial, human, and social capital perspectives in explaining SME growth.